2011
DOI: 10.1088/1742-6596/291/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

A study of structure formation in Ti-Nb-Zr shape memory alloys for medical application

Abstract: Abstract.A study of structure formation in Ti-Nb-Zr shape memory alloys was carried out by means of transmission electron microscopy. After 450 о С annealing of cold-worked specimens a very high dislocation density (10 11 сm -2 ) remained; after 600 о С annealing a mixed structure consisting of submicron sized grains and subgrains formed. Therefore, a nanosubgrained structure is expected to form after 500 -550 о С annealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…They contain exclusively biocompatible components, thus providing high corrosion resistance and biochemical compatibility [1][2][3][4][5], whereas their superelastic behavior and low Young's modulus are close to those of bone tissues [6][7][8][9]. The structure and functional properties of these alloys depend on a complex sequence of phase transformations, including reversible β ↔ α″ and β ↔ ω transformations, and can effectively be controlled by a technological sequence comprising plastic deformation, post-deformation annealing (PDA) and age-hardening heat treatments [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…They contain exclusively biocompatible components, thus providing high corrosion resistance and biochemical compatibility [1][2][3][4][5], whereas their superelastic behavior and low Young's modulus are close to those of bone tissues [6][7][8][9]. The structure and functional properties of these alloys depend on a complex sequence of phase transformations, including reversible β ↔ α″ and β ↔ ω transformations, and can effectively be controlled by a technological sequence comprising plastic deformation, post-deformation annealing (PDA) and age-hardening heat treatments [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Although titanium‐based materials are ones among the most corrosion‐resistant materials in human body fluids, over time the concern related to corrosion phenomenon is still actual . In order to avoid stress shielding effect the low modulus Ti alloys were recently developed for structural biomedical applications . Among these alloys there are ones from TiNbZrAl alloy system , which remark through superelastic properties for certain chemical compositions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the transformation takes place in bulk materials after a severe deformation and different heat treatments when the grain size of the alloy is around 40 nm [9][10][11][12][13] . The development of SMA with controlled grain size is interesting for applications.…”
Section: Introductionmentioning
confidence: 99%